Social Support and Optimism Associated with Student Subjective Well Being: Dukungan Sosial dan Optimisme yang Berkaitan dengan Kesejahteraan Subjektif Siswa - Nur Fajriatus Tsani; Nurfi Laili (Academia Open, 2025)
General Background: Final-year senior high school students face academic and psychological demands requiring adaptive coping resources to maintain positive psychological functioning. Specific Background: Grade XII students often experience anxiety and stress related to graduation examinations and future educational decisions, which may contribute to negative emotional conditions. Knowledge Gap: Empirical evidence regarding the combined relationship between social support, optimism, and subjective well-being among Indonesian final-year students remains limited. Aims: This study examined the relationship between social support and optimism with subjective well-being among grade XII students at SMAN 3 Sidoarjo. Results: Using a quantitative correlational design involving 191 students, data were collected through adapted subjective well-being, social support, and optimism scales. Multiple correlation analysis showed a significant positive relationship between social support and optimism with subjective well-being, with an R square value of 0.268. Partial correlation analysis also showed significant positive relationships between social support and subjective well-being (r = 0.321, p < 0.05) and optimism and subjective well-being (r = 0.460, p < 0.05). Novelty: This study provides quantitative evidence of the combined and partial relationships between psychosocial resources and student subjective well-being in Indonesian secondary education. Implications: The findings support strengthening social and psychological support systems within schools and families to promote positive student psychological conditions. Highlights: Combined Psychosocial Variables Explained 26.8 Percent of Psychological Condition Variance. Peer and Environmental Assistance Showed Moderate Association With Positive Life Evaluation. Positive Expectation Toward Future Conditions Demonstrated Stronger Statistical Correlation Than Interpersonal Assistance. Keywords: Social Support, Optimism, Subjective Well-Being, High School Students, Correlational Study